2016
DOI: 10.5815/ijmsc.2016.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Fast and Efficient Mac Unit on FPGA

Abstract: Floating-point arithmetic operations on digital systems have become an important aspect of research in recent times. Many architecture have been proposed and implemented by various researchers and their merits and demerits are compared. Floating point numbers are first converted into the IEEE 754 single or double precision format in order to be used in the digital systems. The arithmetic operations require various steps to be followed for the correct and accurate steps. In the proposed approach a fast and area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In [7] authors have reported a fast and area efficient carry select adder, that is implemented for exponent addition in floating-point multiplier along with the parallel processing of various units used in the architecture. The result shows a decrement of 27 % in the combinational path delay with an increment of around 8% in the number of LUTs used in comparison to other works discussed in paper.…”
Section: Introductionmentioning
confidence: 99%
“…In [7] authors have reported a fast and area efficient carry select adder, that is implemented for exponent addition in floating-point multiplier along with the parallel processing of various units used in the architecture. The result shows a decrement of 27 % in the combinational path delay with an increment of around 8% in the number of LUTs used in comparison to other works discussed in paper.…”
Section: Introductionmentioning
confidence: 99%